The Effect Of Transformational Leadership And Competence On Performance Through Compensation As An Intervening Variable - Amin, Mat; Wicaksana, Hangga; Suhardi, Suhardi (International Journal of Science, Technology & Management, 2023)
This study aims to determine and analyze the influence of leadership and competence on employee performance, locus of study at Bapedalitbangda Pangkalpinang City, with a total of 53 respondents. Data collection was carried out by distributing questionnaires, with data processing techniques using the PLS SEM model. From the test results, it was found that leadership style has a positive and significant effect on performance and compensation. Compensation has a positive and significant effect on performance, but competence has a positive but not significant effect on performance. Compensation has a positive but not significant effect on compensation. The effect of leadership style on performance with compensation as an intervening variable has a positive and significant effect, and the effect of competence on performance with compensation as an intervening variable shows positive results but not significantly. In improving the performance of Bappedalitbangda Pangkalpinang City employees, it is better to pay more attention to leadership style, increase competence, improve compensation so that it has a significant influence in improving employee performance according to performance evaluation and their respective duties and functions.